Thin-Fiber-Based Fabry–Pérot Cavity for Monitoring Microfluidic Refractive Index - Xiaoling Ni; Songnian Fu; Zhiyong Zhao (IEEE Photonics Journal)
We report an all-fiber miniature exposed Fabry–Pérot (F–P) cavity microfluidic refractometer by splicing an ultrashort segment of thin fiber with standard single-mode fiber with large off-center alignment. Theoretical investigations of dynamic range and sensitivity issues for the proposed fiber sensors are carried out. The exposed F–P cavity can provide excellent interaction between embedded gas/liquid with guided light, with a high sensitivity of 1086 nm/RIU at ∼1550 nm within the refractive index (RI) range from 1.332 to 1.3565. Meanwhile, the exposed F–P cavity structure is insensitive to temperature fluctuation. The simple and cheap fabrication method, together with ultracompact package, stable operation, and low-temperature cross-sensitivity, verify that it has great potential for microfluidic RI sensing for chemical, biological, and medical applications.